A ciência geográfica no helenismo: I -As mitografias de Gaia. - Antonio Carlos Vitte; Marcio Mello Pereira (Confins)
This article aims to discuss the participation of the myth of Gaia in the formation of geographical science in antiquity. For this purpose, Homer´s The Iliad and the Odyssey, the Homeric Hymns, The origin of the world and the gods according Hesiod's Theogony and the Orphic manuscripts have been used in order to understand the role of the Gaia myth in the construction of the first geographical interpretation related to Earth's origin and transformation, allowing the development of science in antiquity. The initial focus was directed to search the pre-Socratic understanding of the physiology and physiography of Gaia while the concept of Kosmos arose, decreeing the end of Gaia. It was from the architecture that Geographical science has developed in Hellenism taking for granted its peak moment in the work of Theophrastus and Strabo that notable influenced the constitution of geographical science in modernity.